2007
DOI: 10.1155/2007/60803
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Dynamics Model of Emotional Memory Processing: A Synthesis on the Neurobiological Basis of Stress-Induced Amnesia, Flashbulb and Traumatic Memories, and the Yerkes-Dodson Law

Abstract: We have reviewed research on the effects of stress on LTP in the hippocampus, amygdala and prefrontal cortex (PFC) and present new findings which provide insight into how the attention and memory-related functions of these structures are influenced by strong emotionality. We have incorporated the stress-LTP findings into our “temporal dynamics” model, which provides a framework for understanding the neurobiological basis of flashbulb and traumatic memories, as well as stress-induced amnesia. An important featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
529
2
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(571 citation statements)
references
References 444 publications
(623 reference statements)
32
529
2
8
Order By: Relevance
“…Their physiological arousal becomes probably more proportional to the complexity of the task and reflects cognitive and emotional activation to engage in the task and to respond with learned communication skills to task challenges. These results are similar with results of other studies that have shown a link between performance and arousal [24][25][26][27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their physiological arousal becomes probably more proportional to the complexity of the task and reflects cognitive and emotional activation to engage in the task and to respond with learned communication skills to task challenges. These results are similar with results of other studies that have shown a link between performance and arousal [24][25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…Moderate physiological arousal levels may therefore result in optimal performance, whereas too little or too much arousal may result in sub-optimal performances [23][24][25][26]. Physiological arousal levels have also been shown to be related to individuals' appraisal of their ability to perform a given task: when individuals perceive that they are unable to perform a complex task (threat appraisal), they may experience difficulties in engaging themselves in the task and their physiological arousal levels remain low, whereas when individuals perceive that they are able to perform a complex task, they experience less difficulties in engaging themselves in the task and their physiological arousal levels remain elevated (challenge appraisal) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This inverted U curve was described by Yerkes and Dodson, and is associated with the learning of difficult tasks. 13 In our study, there was a linear correlation in the IM PGY-2 year for the inpatient and subspecialty experiences, such that each additional 50 patient encounters was associated with an increase of 1 % correct on the ITE. The increase associated with the average of 263 patient encounters would be 5 % more correct on the ITE, which is consistent with the national average year-to-year increase in ITE score.…”
Section: Discussionsupporting
confidence: 47%
“…There appears to be a narrow range for optimal norepinephrine (Aston-Jones & Cohen, 2005) and dopamine activity in the PFC (Arnsten & Goldman-Rakic, 1998;Murphy, Arnsten, Goldman-Rakic, & Roth, 1996;Zahrt, Taylor, Mathew, &Arnsten, 1997). In addition, stress effects are rapid in the PFC (Diamond, Campbell, Park, Halonen, & Zoladz, 2007;Lupien, Gillin, & Hauger, 1999;Roozendaal, McReynolds, McGaugh, 2004) it is inhibited under high stress immediately, unlike the gradual hippocampal inhibition, and remains inhibited as long as stress hormones are secreted (Diamond, Campbell, Park, Halonen, & Zoladz, 2007).…”
Section: Effects Of Stress On Memory-related Brain Regionsmentioning
confidence: 99%